Dentinogenesis imperfecta in a 6-year-old male neutered Labrador retriever: Case report with atypical clinical presentation and treatment review - Piekos, Karolina Maria; Freeman, Alix; Fleming, Kathryn; Bell, Cynthia (Frontiers in Veterinary Science, 2024)
This case report details the diagnosis and treatment of dentinogenesis imperfecta in a 6-year-old neutered male Labrador, presenting without concurrent osteogenesis imperfecta. Diagnostic modalities, including radiographs, CT imaging, and histopathological examination, are reviewed in conjunction with the latest literature on canine dentinogenesis imperfecta. This patient presented at a more advanced age than typically reported cases. The clinical history, as provided by referring veterinarians, documented fractured deciduous teeth with delayed exfoliation. By 10 months of age, the patient’s permanent dentition exhibited a translucent appearance and structural anomalies. Upon presentation to Eastcott Referrals the patient was experiencing significant oral pain and exhibited generalised coronal wear with yellow/brown intrinsic discolouration. CT imaging revealed that all teeth had endodontic disease and associated apical periodontitis, with varied root canal widths indicating that teeth succumbed to endodontic disease at different time points. The treatment protocol involved staged full-mouth extractions, resulting in the complete resolution of clinical symptoms. This case underscores the importance of early diagnosis and intervention in managing dentinogenesis imperfecta in dogs.